Global burden of viral skin diseases from 1990 to 2021: a systematic analysis for the global burden of disease study 2021 - Li, Deng; Chen, Ming; Li, Wei; Xu, Xuewen; Li, Qingfeng (Frontiers in Public Health, 2025)
BackgroundThe scarcity of knowledge regarding the epidemiology and temporal patterns of viral skin diseases worldwide poses significant challenges to their control and management.MethodsWe analyzed the global incidence, prevalence, and age-standardized rates (ASR) of disability-adjusted life years (DALYs) for viral skin diseases in 2021. To examine temporal trends from 1990 to 2021, we employed the EPAC model, assessing changes by country, gender, age, Socio-demographic Index (SDI), and GBD regions. Additionally, we utilized the age-period-cohort (APC) model and the Bayesian age-period-cohort (BAPC) model to forecast the burden of viral skin diseases for the next 25 years.ResultsIn 2021, the global burden of viral skin diseases was estimated at 84.7 million incident cases, with a prevalence of over 130 million cases and 4.2 million DALYs. Males experienced a slightly higher ASR burden than females. The highest burden was observed among individuals aged 10 to 19, with significant geographical variations in cases and ASR, particularly in high SDI regions. Unexpected rises in incidence were noted in East Asia and Sub-Saharan Africa in the detected period. Despite modest declines in ASPR and ASDR, the global ASIR displayed a significant upward trend.ConclusionOur study provides detailed data on the global impact of viral skin diseases from 1990 to 2021, highlighting the need for continuous surveillance and tailored interventions to manage and reduce the effects of these diseases. Targeted public health measures are essential to address and mitigate the global health burden of viral skin diseases.